Three PWM based Control Technics for Switched Boost Inverter - Elshan Davaranhagh; Ebrahim Babaei; Mehran Sabahi; Sima Shahmohamadi (Majlesi Journal of Electrical Engineering, 2023)
Switched Boost Inverter (SBI) operates in buck-boost mode with an extensive spectrum of output voltage obtainable from a specific source voltage. Also, this structure provides superior protection against Electromagnetic Wave Interference (EMI) juxtaposed with the traditional impedance source inverter. The number of energy storage elements in this structure has been reduced, which increases the efficiency of the converter in low-power applications, reducing cost, size, and weight. In this paper, this inverter is analyzed and investigated in different operating modes and steady-state. Also, three different pulse width modulation (PWM) control techniques are presented for this inverter. Simulation results are presented in PSCAD-EMTDC software to validate the calculated relationships and confirm their performance in three different switching methods.